2014
DOI: 10.1016/j.celrep.2014.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Alterations in Gut Microflora Contribute to Lethal Pulmonary Damage in TLR2/TLR4-Deficient Mice

Abstract: SUMMARY Chronic intake of Western diet has driven an epidemic of obesity and metabolic syndrome, but how it induces mortality remains unclear. Here we show that chronic intake of a high-fat diet (HFD), not a low-fat diet (LFD), leads to severe pulmonary damage and mortality in mice deficient in Toll-like receptors (TLR) 2 and 4 (DKO hereafter). Diet-induced pulmonary lesions are blocked by antibiotics treatment and transmissible to wildtype mice upon either cohousing or fecal transplantation, pointing to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 60 publications
(85 reference statements)
3
30
0
Order By: Relevance
“…Consistent with our findings that the gut microbiota can also influence systemic (i.e., lung) inflammation and tissue damage, it has been shown that increased circulating bacterial toxins result in reduced tight junction gene expression and lethal pulmonary damage following fecal transplantation (Ji et al., 2014). The authors suggest that these changes may occur following overgrowth of gut microbes and/or threshold production of bacterial products, resulting in their systemic translocation, increased inflammation, and ensuing pulmonary endothelial damage.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings that the gut microbiota can also influence systemic (i.e., lung) inflammation and tissue damage, it has been shown that increased circulating bacterial toxins result in reduced tight junction gene expression and lethal pulmonary damage following fecal transplantation (Ji et al., 2014). The authors suggest that these changes may occur following overgrowth of gut microbes and/or threshold production of bacterial products, resulting in their systemic translocation, increased inflammation, and ensuing pulmonary endothelial damage.…”
Section: Discussionsupporting
confidence: 92%
“…Flow cytometric analysis of peripheral immune cells was performed as we previously described (Ji et al, 2014; Ji et al, 2012). To isolate bone marrow (BM), tibia and femurs were isolated from mice and BM was flushed using cold PBS supplemented with 5% FBS and 1% penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Tlr4 -/-mice fed a HFD demonstrated reduced intestinal permeability, increased plasma endotoxin and proinflammatory cytokine levels, and increased epididymal fat weight 84 . Interestingly, chronic intake of a HFD leads to severe pulmonary damage and mortality in Tlr2 -/-Tlr4 -/-mice 85 , suggesting that diet and innate immune deficiency have a strong impact on the composition of the gut microbiota, which can lead to life-threatening conditions.…”
Section: [H3] Gut Microbiotamentioning
confidence: 99%